The Analysis And Design of School Health Unit Information System - Dhiani Tresna Absari; Liliana Liliana (Jurnal Komputer Terapan, 2021)
The success of education is supported by both academic and non-academic aspects. To achieve this educational goal, schools should have a good partnership with parents regarding both aspects, including student health. But unfortunately, many school considers student health unit which is called Usaha Kesehatan Sekolah (UKS) as a supporting system in their business processes at school, and it gets less attention. Currently, quite a lot of activities at UKS are carried out on a paper-based process, or even rely on the memory of officers, such as permission not to go to school, use of drugs, information on outreach activities, things that happen to the children at school and other activities. Such information may not be well received by parents. Therefore, a system that allows parents and schools to interact online is needed, regarding children's health conditions while in school and otherwise. This system is designed in two platforms, which are web and mobile; and centralized in one database, so that the system remains integrated and can be accessed easily by the school and parents. Thus, this system is expected to improve the quality of communication between schools and parents.